Genetic prediction of blood metabolites mediating the relationship between gut microbiota and Alzheimer’s disease: a Mendelian randomization study - Chen, Guanglei; Jin, Yaxian; Chu, Cancan; Zheng, Yuhao; Chen, Yunzhi; Zhu, Xing (Frontiers in Microbiology, 2024)
Background Observational studies have suggested an association between gut microbiota and Alzheimer’s disease (AD); however, the causal relationship remains unclear, and the role of blood metabolites in this association remains elusive. Purpose To elucidate the causal relationship between gut microbiota and AD and to investigate whether blood metabolites serve as potential mediators. Materials and methods Univariable Mendelian randomization (UVMR) analysis was employed to assess the causal relationship between gut microbiota and AD, while multivariable MR (MVMR) was utilized to mitigate confounding factors. Subsequently, a two-step mediation MR approach was employed to explore the role of blood metabolites as potential mediators. We primarily utilized the inverse variance-weighted method to evaluate the causal relationship between exposure and outcome, and sensitivity analyses including Contamination mixture, Maximum-likelihood, Debiased inverse-variance weighted, MR-Egger, Bayesian Weighted Mendelian randomization, and MR pleiotropy residual sum and outlier were conducted to address pleiotropy. Results After adjustment for reverse causality and MVMR correction, class Actinobacteria (OR: 1.03, 95% CI: 1.01–1.06, p = 0.006), family Lactobacillaceae (OR: 1.03, 95% CI: 1.00–1.05, p = 0.017), genus Lachnoclostridium (OR: 1.03, 95% CI: 1.00–1.06, p = 0.019), genus Ruminiclostridium9 (OR: 0.97, 95% CI: 0.94–1.00, p = 0.027) and genus Ruminiclostridium6 (OR: 1.03, 95% CI: 1.01–1.05, p = 0.009) exhibited causal effects on AD. Moreover, 1-ribosyl-imidazoleacetate levels (−6.62%), Metabolonic lactone sulfate levels (2.90%), and Nonadecanoate (19:0) levels (−12.17%) mediated the total genetic predictive effects of class Actinobacteria on AD risk. Similarly, 2-stearoyl-GPE (18:0) levels (−9.87%), Octadecanedioylcarnitine (C18-DC) levels (4.44%), 1-(1-enyl-stearoyl)-2-oleoyl-GPE (p-18:0/18:1) levels (38.66%), and X-23639 levels (13.28%) respectively mediated the total genetic predictive effects of family Lactobacillaceae on AD risk. Furthermore, Hexadecanedioate (C16-DC) levels (5.45%) mediated the total genetic predictive effects of genus Ruminiclostridium 6 on AD risk; Indole-3-carboxylate levels (13.91%), X-13431 levels (7.08%), Alpha-ketoglutarate to succinate ratio (−13.91%), 3-phosphoglycerate to glycerate ratio (15.27%), and Succinate to proline ratio (−14.64%) respectively mediated the total genetic predictive effects of genus Ruminiclostridium 9 on AD risk. Conclusion Our mediation MR analysis provides genetic evidence suggesting the potential mediating role of blood metabolites in the causal relationship between gut microbiota and AD. Further large-scale randomized controlled trials are warranted to validate the role of blood metabolites in the specific mechanisms by which gut microbiota influence AD.